Plant Ontology (PO): a Controlled Vocabulary of Plant Structures and Growth Stages. Issue 7 (2005) - Jaiswal, Pankaj; Avraham, Shulamit; Ilic, Katica; Kellogg, Elizabeth A.; McCouch, Susan; Pujar, Anuradha; Reiser, Leonore; Rhee, Seung Y.; Sachs, Martin M.; Schaeffer, Mary; Stein, Lincoln; Stevens, Peter; et al.
Abstract : The Plant Ontology Consortium (POC) (www.plantontology.org) is a collaborative effort among several plant databases and experts in plant systematics, botany and genomics. A primary goal of the POC is to develop simple yet robust and extensible controlled vocabularies that accurately reflect the biology of plant structures and developmental stages. These provide a network of vocabularies linked by relationships (ontology) to facilitate queries that cut across datasets within a database or between multiple databases. The current version of the ontology integrates diverse vocabularies used to describe Arabidopsis, maize and rice ( Oryza sp.) anatomy, morphology and growth stages. Using the ontology browser, over 3500 gene annotations from three species-specific databases, The Arabidopsis Information Resource (TAIR) for Arabidopsis, Gramene for rice and MaizeGDB for maize, can now be queried and retrieved.